Self-isolation of Healthcare Workers during COVID-19 Pandemic in a Tertiary Care Center – Association between their Sleep Quality, Anxiety Status and Social Capital - Avik Kumar Layek; Nilanjana Ghosh; Jagadish Biswas; SpandanBhaduri (Indian Journal of Forensic Medicine & Toxicology, 2021)
With the rapid spread of COVID-19 since its inception a year back, the frontline healthcare workers, who underwent isolation and quarantine following possible exposure, faced multiple psychiatric problems like deterioration of sleep quality and anxiety manifestations. Different demographic variables were found to be associated with their occurrence, as well as inter-relation between them were found to be common. We tried to examine the role of social support system as well to the appearance of such problems in the present study. After getting the ethical clearance, willing healthcare workers during their isolation and quarantine were presented questionnaires consisting of Socio-demographic proforma, Self-rating Anxiety Scale (SAS), Personal Social Capital Scale 16 (PSCS) and Pittsburgh Sleep Quality Index (PSQI). Data taken were analysed with independent t test and Fishers exact chi square test, Pearson’s correlation analysis and linear regression analysis. Majority of the subjects were married Hindu female from urban background, mostly doctor and nurse by profession. Independent T test revealed significant association between gender and anxiety status as well as between marital status and sleep quality. Positive correlation between the PSCS scores and the SAS scores (r=0.652, P<0.01) and negative correlations between the PSCS and PSQI scores and between the SAS and PSQI score were found albeit being statistically insignificant. Significant association was found between the SAS score and social bridging component of PSCS (Fishers exact chi sq. value 0.54 and p = 0.003). Anxiety score was significantly affected when the socio-demographic factors like gender, religion, marital status and scores of sleep quality (PSQI) and social capital (PSCS) were considered together as seen in the linear regression analysis.